No Improvement of Survival for Alveolar Rhabdomyosarcoma Patients After HLA-Matched Versus -Mismatched Allogeneic Hematopoietic Stem Cell Transplantation Compared to Standard-of-Care Therapy - Schober, Sebastian Johannes; Hallmen, Erika; Reßle, Florian; Gassmann, Hendrik; Prexler, Carolin; Wawer, Angela; von Luettichau, Irene; Ladenstein, Ruth; Kazanowska, Bernarda; Ljungman, Gustaf; Niggli, Felix; Lohi, Olli; et al. (Frontiers in Oncology, 2022)
Background: Patients with stage IV alveolar rhabdomyosarcoma (RMA) have 5-year-survival rate not exceeding 30%. Here we assess the role of allogeneic hematopoietic stem cell transplantation (allo-HSCT) for these patients in comparison to standard of care regimens. We also compare the use of HLA-mismatched vs. HLA-matched grafts after reduced - vs. myeloablative conditioning regimens, respectively. Patients and Methods: In this retrospective analysis, we compare event-free survival (EFS), overall survival (OS) and toxicity of HLA-mismatched vs. -matched transplanted patients in uni- and multivariate analyses (total: n=50, HLA-matched: n=15, HLA-mismatched: n=35). Here, the factors age at diagnosis, age at allo-HSCT, sex, Oberlin score, disease status at allo-HSCT, and HLA graft type are assessed. For 29 primarily transplanted patients, three matched non-transplanted patients per one transplanted patient were identified from the CWS registry. Outcomes were respectively compared for OS and EFS. Matching criteria included sex, age at diagnosis, favorable/unfavorable primary tumor site, metastatic sites. Results: Median EFS and OS did not differ significantly between HLA-mismatched and -matched patients. In the mismatched group, incidence of acute GvHD was 0.87 (grade III-IV: 0.14) vs. 0.80 in HLA-matched patients (grade III-IV: 0.20). Transplant-related mortality (TRM) of all patients was 0.20 and did not differ significantly between HLA-mismatched and -matched groups. A proportion of 0.58 relapsed or progressed and died of disease (HLA-mismatched: 0.66, HLA-matched: 0.53) whereas 0.18 were alive in complete remission (CR) at data collection. Multivariate and competing risk analyses confirmed CR and very good partial response (VGPR) status prior to allo-HSCT as the only decisive predictor for OS (p<0.001). Matched-pair survival analyses of primarily transplanted patients vs. matched non-transplanted patients also identified disease status prior allo-HSCT (CR, VGPR) as the only significant predictor for EFS. Here, OS was not affected, however. Conclusion: In this retrospective analysis, only a subgroup of patients with good response at allo-HSCT survived. There was no survival benefit of allo-transplanted patients compared to matched controls, suggesting the absence of a clinically relevant graft-vs.-RMA effect in the current setting. The results of this analysis do not support further implementation of allo-HSCT in RMA stage IV patients.